2017
DOI: 10.1177/2056305117727637
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Predictors of Participation in Facebook Pictivism Campaigns

Abstract: Several events in recent years have motivated Facebook users to change their profile pictures to raise awareness about an issue within their network (Cofff, Chapman, & Coffé, 2016). For instance, when the Human Rights Campaign urged people to change their profile photos to a pink equal sign in support of marriage equality in 2013, 120% more profile picture changes were made than usual (Bakshy, 2013). Then, within days of the US Supreme Court's ruling to legalize same-sex marriage in 2015, over 26 million Faceb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Besides, numerous studies asserted that attitude directs the decision making process and influences behavior (Bohner & Dickel, 2011;Lee & An, 2018). Therefore, studies have identified that positive attitude towards a social media platform encourages users to like, comment and share which is considered as positive sharing behavior by users on that media platform (Oeldorf-Hirsch & McGloin, 2017). Based on the above discussion, the authors of this study put forward the following hypothesis:…”
Section: Effect Of Information Sharing Attitude On Information Sharin...mentioning
confidence: 86%
“…Besides, numerous studies asserted that attitude directs the decision making process and influences behavior (Bohner & Dickel, 2011;Lee & An, 2018). Therefore, studies have identified that positive attitude towards a social media platform encourages users to like, comment and share which is considered as positive sharing behavior by users on that media platform (Oeldorf-Hirsch & McGloin, 2017). Based on the above discussion, the authors of this study put forward the following hypothesis:…”
Section: Effect Of Information Sharing Attitude On Information Sharin...mentioning
confidence: 86%
“…From movements like #BlackLivesMatter to #MeToo, social media has provided marginalized groups with a space to gain visibility (Shahin et al, 2021). However, critics argue that social media activism can also lead to what is often referred to as “slacktivism” (Morozov, 2009, p. 7), “clicktivism” (Halupka, 2018), or “pictivism” (Oeldorf-Hirsch & McGloin, 2017). Instead of generating meaningful participation, social media may result in superficial and unhelpful forms of engagement (Morozov, 2009).…”
Section: Online Activism and Social Mediamentioning
confidence: 99%
“…In terms of online displays of support for LGBTQ issues, people use social media in various ways (e.g., hashtags, rainbow flag emojis) to mark themselves as LGBTQ or as allies. As a particularly prevalent behavior, changing one’s profile picture or adopting a profile filter—a low effort behavior called “pictivism” (Oeldorf-Hirsch & McGloin, 2017)—emerged as a popular way for internet users to express pro-LGBTQ political support and raise awareness (Chapman & Coffé, 2015). For example, approximately 3 million Facebook users changed their pictures to the Human Rights Campaign’s equality sign logo in light of marriage equality cases in 2013, and 26 million users adopted the rainbow flag filter to celebrate nationwide same-sex marriage rights in 2015 (Dewey, 2015; State & Adamic, 2015).…”
Section: Social Media and Lgbtq Activismmentioning
confidence: 99%